1998
DOI: 10.1017/s0144686x98006928
|View full text |Cite
|
Sign up to set email alerts
|

The discourse of self in dementia

Abstract: The preservation of self-identity in dementia is dependent upon internal (cognitive) and external (social) conditions. This study investigates the integrity of self (internal) and personae (external) in dementia as indexed by the verbal and nonverbal behaviours of dementia residents and their caregivers in a special care unit. Videotaped observations of spontaneous nursing staff-resident interactions were collected over a three-day period. The recordings were transcribed and subjected to detailed di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
52
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(55 citation statements)
references
References 18 publications
3
52
0
Order By: Relevance
“…(1998) hold the view that the internal identity (the self) remains intact within patients with dementia despite cognitive impairments, but that the loss of their external identity (personae) – which is mutually constructed when each person relates to the other – could be preserved. Our findings are in line with those of Small et al. (1998), who argue that carers can help patients preserve their personae (external identity) by taking interest in their backgrounds, lived experiences and acknowledging their expressions of needs, wishes and resources.…”
Section: Supervision To Develop Personal and Professional Skills In Nsupporting
confidence: 91%
See 1 more Smart Citation
“…(1998) hold the view that the internal identity (the self) remains intact within patients with dementia despite cognitive impairments, but that the loss of their external identity (personae) – which is mutually constructed when each person relates to the other – could be preserved. Our findings are in line with those of Small et al. (1998), who argue that carers can help patients preserve their personae (external identity) by taking interest in their backgrounds, lived experiences and acknowledging their expressions of needs, wishes and resources.…”
Section: Supervision To Develop Personal and Professional Skills In Nsupporting
confidence: 91%
“…Thus, our findings could be interpreted as indicating that carers, in their interactions with patients, improved in preserving patients’ identity and sense of dignity. Sabat and Harré (1992), Mills and Coleman (1994), and Small et al. (1998) hold the view that the internal identity (the self) remains intact within patients with dementia despite cognitive impairments, but that the loss of their external identity (personae) – which is mutually constructed when each person relates to the other – could be preserved.…”
Section: Supervision To Develop Personal and Professional Skills In Nmentioning
confidence: 99%
“…In particular, activities relating to self-identity (e.g., occupation or family role) can successfully promote involvement, decrease agitation, increase positive emotional responses, and reduce disorientation (Cohen-Mansfield, Parpura-Gill, & Golander, 2006a). Small, Geldart, Gutman, and Scott (1998) found that personalized interactions between staff members and residents elicited more involvement and cooperative responses by residents than did nonpersonalized interactions. In a study on the effects of personalized, nonpharmacological interventions on agitation, Cohen-Mansfield et al (2007) found that such interventions resulted in statistically significant decreases in overall agitation in the intervention group relative to the control group.…”
Section: Introductionmentioning
confidence: 92%
“…Indeed, Cohen-Mansfield, Parpura-Gill, and Golander (2006) found that when participants with dementia were presented with interventions tailored to their self-identity they were more involved than were control group participants with regular activities. Other studies have also found evidence for the persistence of self-identity in persons with dementia, although it may depend on interactions with others that allow this identity to be expressed (Golander & Raz, 1996; Li & Orleans, 2002; Small, Geldart, Gutman, & Clarke-Scott, 1998; Sabat & Harre, 1992; Tappen, Williams, Fishman, & Touhy, 1999). …”
Section: Introductionmentioning
confidence: 98%